HUBUNGAN SUPERVISI KEPALA RUANGAN TERHADAP KEPUASAN KERJA PERAWAT PELAKSANA DI RUMAH SAKIT IMELDA MEDAN - Basri Basri (Jurnal Maternitas Kebidanan, 2018)
Job nurse executive satisfaction can be influenced by the supervision given by the head of the room. There are many factors related to the function of supervision of the head of the room that can lead to satisfaction or dissatisfaction of nurses at work. The purpose of this study was to analyze the supervision of the head of the room, analyze job satisfaction, and analyze the relationship of head room supervision to job satisfaction of nurses at Imelda Hospital Medan. The design of this study is descriptive correlation. Sampling using the technique of total sampling of 42 implementing nurses. Data collection using questionnaires, data analysis by using the person product moment correlation test technique. The results of the percentage of supplementation were found to be 73.8% satisfied category, while the satisfaction of nurses' emotional reaction to their work was stated to be 73.8% satisfied. Pearson product moment correlation of head room supervision test with nurse job satisfaction showed p = .012 significant with r = 0.384. This study shows that there is a relationship between supervision and job satisfaction of nurses at the Imelda Hospital in Medan. The thing that needs to be presented in this study is to optimize the supervisor's role by implementing programmed and scheduled supervision activities to increase emotional reactions and the attitude of nurses to their work